Characterization of Chitinolytic and Antifungal Activities in Marine-Derived Trichoderma bissettii Strains. Issue 4 (4th July 2022) - Chung, Dawoon; Kwon, Yong Min; Lim, Ji Yeon; Bae, Seung Sub; Choi, Grace; Lee, Dae-Sung
Abstract: Trichoderma fungi have been intensively studied for mycoparasitism, and the latter is closely related to their cell-wall degrading enzymes including chitinase. Here, we studied marine-derived Trichoderma spp., isolated from distinct sources and locations, for chitinolytic and antifungal activity. Based on morphological and phylogenetic analyses, two strains designated GJ-Sp1 and TOP-Co8 (isolated from a marine sponge and a marine alga, respectively) were identified as Trichoderma bissettii . This species has recently been identified as a closely related species to Trichoderma longibrachiatum . The extracellular crude enzymes of GJ-Sp1 and TOP-Co8 showed activities of chitobiosidase and β-N-acetylglucosaminidase (exochitinase) and chitotriosidase (endochitinase). The optimum chitinolytic activity of the crude enzymes was observed at 50 °C, pH 5.0, 0–0.5% NaCl concentrations, and the activities were stable at temperatures ranging from 10 to 40 °C for 2 h. Moreover, the crude enzymes showed inhibitory activity against hyphal growth of two filamentous fungi Aspergillus flavus and Aspergillus niger . To the best of our knowledge, this is the first report of the chitinolytic and antifungal activity of T . bissettii .